2013
DOI: 10.1002/ange.201301363
|View full text |Cite
|
Sign up to set email alerts
|

Silicon(II) Coordination Chemistry: N‐Heterocyclic Carbene Complexes of Si2+ and SiI+

Abstract: Der Austausch von N‐heterocyclischen Carbenliganden (NHC) an SiII‐Zentren öffnet einen Zugang zu einem dikationischen NHC‐Komplex von Silicium(II) sowie zu [SiI(IiPr2Me2)(IDipp)]+, einem NHC‐Addukt des Iodsilyliumyliden‐Kations SiI+ (siehe Bild). Im Zuge von Charakterisierungsstudien wurde eine beispiellose anagostische CH⋅⋅⋅Si‐Wechselwirkung in [SiI(IiPr2Me2)(IDipp)]+ entdeckt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 66 publications
(35 reference statements)
0
13
0
2
Order By: Relevance
“…Angesichts der aktuellen Diskussion über den Gebrauch von Pfeilen für die Darstellung von Donor-Akzeptor-Bindungen [16] [17] oder an das Siliciumzentrum der Si=Ge-Bindung koordinieren kçnnte. [18] Rechnungen auf dem wB97XD/6- [12,13] was stattdessen auf die Bildung eines Dreiringes, ähnlich den NHC-koordinierten Cyclopropyildenen 4, schließen lässt.…”
Section: Cyclopropeneunclassified
“…Angesichts der aktuellen Diskussion über den Gebrauch von Pfeilen für die Darstellung von Donor-Akzeptor-Bindungen [16] [17] oder an das Siliciumzentrum der Si=Ge-Bindung koordinieren kçnnte. [18] Rechnungen auf dem wB97XD/6- [12,13] was stattdessen auf die Bildung eines Dreiringes, ähnlich den NHC-koordinierten Cyclopropyildenen 4, schließen lässt.…”
Section: Cyclopropeneunclassified
“…Key to these developments have been the usage of suitable synthetic methodologies in combination with thermodynamic and kinetic stabilization by appropriately chosen ligands. In particular, for the heavier carbon analogue silicon, a plethora of studies reported new low-valent compounds in recent years [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and the chemistry of silylene base adducts has already been carefully developed [14,[26][27][28][29][30][31][32][33][34][35][36]. Before these findings, silyliumylidene ions, cationic Si(II) species were found to be promising as similar versatile Lewis amphiphiles [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…As NHCs are strong σ donors, donors, their application in main group chemistry enabled the isolation of a large variety of low coordinate and low-valent main group compounds [41,42]. The first NHC-stabilized silyliumylidenes, III and IV were synthesized by Filippou and coworkers via a three-step protocol from SiI4 [28], and by Driess and coworkers through the reaction of Roesky's NHC-stabilized dichlorosilylene with their bridged bis-carbene ligand [23].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, some arylbromosilylidene and arylsilylidyne complexes of nickel and platinum were reported [32][33][34]. In 2013, Filippou's group reported the unprecedented dicationic NHC complexes of silicon(II) and NHC adducts of iodesilyliumylidene cation SiI + [35]. Subsequently, we reported the reaction of 1,2-dibromodisilenes (1b, 1e, and 1f) having EMind, Bbt, and Tbb groups (Tbb = 2,6-{CH(SiMe3)2}2-4-t Bu-C6H2 (f)) with NHCs (Im-Me4 and Im-i Pr2Me2) (Im-i Pr2Me2 = 1,3-diisopropyl-4,5-dimethylimidazol-2-ylidene) leading to the formation of mono-NHC adducts of arylbromosilylenes, NHC→SiBr(Ar) (VIb′ and VIe), and the bromide salts of the bis-NHC adducts of formal arylsilyliumylidene cations, [(NHC)2 →Si(Ar)] + [Br − ] (VIIb, VIIb′, and VIIf) [22].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, some arylbromosilylidene and arylsilylidyne complexes of nickel and platinum were reported [32][33][34]. In 2013, Filippou's group reported the unprecedented dicationic NHC complexes of silicon(II) and NHC adducts of iodesilyliumylidene cation SiI + [35]. Subsequently, we reported the reaction of 1,2-dibromodisilenes (1b, 1e, and 1f) having EMind, Bbt, and Tbb groups (Tbb = 2,6-{CH(SiMe 3 ) 2 } 2 -4-t Bu-C 6 H 2 (f)) with NHCs (Im-Me 4 [24].…”
Section: Introductionmentioning
confidence: 99%